Influence of capillary condensation on the adsorption of Br2 in flue gas using a super-fine polyester fiber as adsorbent. (10th February 2023) - Xiao, Hanxi; Chi, Yong; You, Yusheng; Ren, Min; Wu, Lufen; Li, Hongli; Li, Manyuan; Shi, Xue; She, Yu; Mao, Dongchan
Abstract: Br2 is the major speciation of Br in flue gas from the combustion of materials containing Br. The route for the recycling of this resource must be highly efficient, which could achieve maximum environmental protection with sound economics. In the present work, adsorption experiments of Br2 in simulated flue gas with a super-fine polyester fiber as adsorbent (SPFa ) were conducted by using a lab-scale fixed bed system, and the real-time adsorbance was continuously monitored. The influence of operating condition and water vapor in flue gas on adsorption efficiency was systematically investigated. SPFa displays exceptional selectivity and remarkable adsorption capability at minimal running cost. At low or sufficiently high Br2 concentration (CBr2 ), capillary condensation dramatically promotes the adsorption rate and equilibrium adsorbance (me ). With mid-range CBr2, at the later stage, the adsorption rate shows reduction, and me shows subtle reduction/minimal increment because of the influence of capillary condensation on the internal diffusion of Br2 . The adsorbent retains a considerable amount of adsorption capacity after the penetration of the bed. The water vapor has no competition with Br2 to develop capillary condensation, in which the low molar density of Br2 has a significant contribution. Based on the results, measures to improve the working efficiency of adsorption devices are proposed.